An unexpected case of coumarin poisoning with coumatetralyl. (13th April 2011) - Kay, Amin; Chiu, Leo; Chong, Christopher AKY
Abstract : A healthy man in his 40s presented with a 1-month history of haemoptysis and was unexpectedly found to have an elevated international normalised ratio (INR). He denied any known exposures to anticoagulants. Testing for the possible aetiologies of a high INR revealed coumarin poisoning with coumatetralyl as the cause. The approach to an elevated INR and management and diagnosis of suspected coumarin poisoning is reviewed.